Estimation of avoidable losses caused by Meloidogyne incognita infecting cucumber in poly-house - Dr. Shakti Singh Bhati Bhati; B L Baheti (Journal of Agriculture and Applied Biology, 2021)
Cucumber (Cucumis sativus L.) is a high nutritious and mineral-rich vegetable, which occupies a prominent place as a salad and vegetable. It is being used in many ways in the daily diet of humans and widely cultivated worldwide. The decrease of agricultural land, adverse environmental conditions and continuous increase of population, the demand of nutritious food is a matter of great concern to the world. Protected cultivation is a very effective tool to solve this problem because in this cultivation the productivity of crops is very high as compared to open field conditions. High value crops successfully grown in protected cultivation, specially vegetables (cucumber, tomato, Capsicum etc.) which are highly susceptible to the numerous pests and pathogens, including phyto-parasitic nematodes (specially root-knot nematode, Meloidogyne spp.). With this view, present trial was taken to estimate the avoidable losses caused by Meloidogyne incognita infecting cucumber in poly-house situated on farmer’s field with the application of phorate at 2 kg a.i. ha-1 over check. Results exhibited that application of chemical treatment significantly reduced number of galls per 5 g roots, egg masses per 5 g roots, eggs & juveniles per egg mass and final nematode population 79.03, 81.10, 30.91 and 56.54%, respectively. Avoidable yield losses were recorded to the tune of 66.84% on cucumber by M. incognita in poly-house.